2012
DOI: 10.3744/jnaoe.2012.4.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Mean flow characteristics of two-dimensional wings in ground effect

Abstract: The present study numerically investigates the aerodynamic characteristics of two-dimensional wings in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…The turbulence is modeled by the realizable k − ε model. 33,34 The setting of calculation zone, boundary conditions and coordinate axis of numerical simulation in this study are shown in Figure 8. The fixed two-dimensional Cartesian coordinate system is adopted.…”
Section: Methodsmentioning
confidence: 99%
“…The turbulence is modeled by the realizable k − ε model. 33,34 The setting of calculation zone, boundary conditions and coordinate axis of numerical simulation in this study are shown in Figure 8. The fixed two-dimensional Cartesian coordinate system is adopted.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, authors and coworkers (Jung et al, 2012) numerically investigated the aerodynamic characteristics of 2D wings in the vicinity of the ground by solving 2D steady incompressible Navier-Stokes equations with the turbulence closure model. In addition, they studied the effects of Reynolds number, and showed that the lift-to-drag ratio increases linearly with an increasing Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…Kayiem and Chelven (2011) presented the aerodynamic characteristics of NACA4412 airfoil using FLUENT software and experimental measurements in low speed wind tunnel from Ϫ4°to 8°in ground effect. Also, Jung et al (2012) investigated aerodynamic characteristics of NACA4406 airfoil using FLUENT software. They found that the maximum lift coefficient increases considerably as the wing approaches the ground.…”
Section: Introductionmentioning
confidence: 99%